2017
DOI: 10.1371/journal.pone.0177070
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of adaptive immunity does not interfere with Wallerian degeneration

Abstract: Following injury, distal axons undergo the process of Wallerian degeneration, and then cell debris is cleared to create a permissive environment for axon regeneration. The innate and adaptive immune systems are believed to be critical for facilitating the clearance of myelin and axonal debris during this process. However, immunodeficient animal models are regularly used in transplantation studies investigating cell therapies to modulate the degenerative/regenerative response. Given the importance of the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…cyclosporine, which would have been required in immune competent mice and its efficacy would have added another factor of variation between individual mice. A study in our lab found axonal regeneration and myelin debris clearance to be comparable between three different mouse strains with deficiencies in the adaptive immune system to that of wild type mice (Cashman and Höke 2017). Naïve cells were used as the control as our in vitro results did not show a significant effect on myelination frequency, proliferation, or apoptosis between naïve and non-transduced cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…cyclosporine, which would have been required in immune competent mice and its efficacy would have added another factor of variation between individual mice. A study in our lab found axonal regeneration and myelin debris clearance to be comparable between three different mouse strains with deficiencies in the adaptive immune system to that of wild type mice (Cashman and Höke 2017). Naïve cells were used as the control as our in vitro results did not show a significant effect on myelination frequency, proliferation, or apoptosis between naïve and non-transduced cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Persistent activation of inflammatory pathways is also a common transcriptional correlate of neuropathic pain in higher-order structures (brain 17 , 43 , spinal cord 44 , 45 , and dorsal root ganglia 46 , 47 ) after peripheral nerve injury. Importantly, although the adaptive immune response to nerve injury is incompletely characterized, previous studies suggest the adaptive immune cells have little impact on the kinetics of WD, and suppression may even may facilitate peripheral nerve regeneration 48 , 49 . Conversely, aberrant activation of adaptive immunity is implicated in chronic pain states, potentially governing steady recruitment of inflammatory species thereby influencing axonal sensitization 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the humoral immune system induced phagocytosis also plays a role in nerve regeneration. However, a more recent study showed that adaptive immunodeficiency Rag −/− had an increase in axonal degeneration and increased healing due to increase in macrophages to compensate for the reduced T and B cells [85]. Given the contrasting and possibly conflicting results between humoral immune system and PNS healing, more studies are needed to confirm their relationship.…”
Section: Autologous and Allogeneic Stem Cellsmentioning
confidence: 99%